Psychomotor abilities in handball. Overview - Muntianu Vlad-Alexandru; Voinea Nicolae-Lucian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
Regardless of the degree of importance given to the instructive-educational process of training, psychomotor behaviours make their presence felt throughout life, theydevelop with varying weights depending on the objectives and tasks we propose. The notions of psychomotor skills are approached in a selective manner in the literature, and following the researchof bibliographic resources we can mention the interest of researchers in these aspects, but another remark can be made about the lack of studies as a whole a clear view of how they make their presence felt in the case of each individual.